PELAKSANAAN MANAJEMEN PESERTA DIDIK PADA MAN BERINGIN KOTA SAWAHLUNTO - Junaidi Junaidi (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This study was aimed at describing the implementation of the management of learners at MAN Beringin Kota Sawahlunto. This study was related to qualitative descriptive to prove the actual object (study phenomena) and was compared from the theory. The findings showed that the implementation of learners’ management generally had been accomplished in accordance with the function of management. For the management of counseling, it was not optimal because it does not have the program and facility.Keywords: Management, Learners, MAN Beringin